2022
DOI: 10.24235/amwal.v14i1.8900
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Business Motivation, Business Competition, and Brand Equity on Business Development with Religiosity as Moderating Variable (Case Study MSMEs Actors in Semarang District)

Abstract: This study aimed to analyze the effect of business motivation, business competition, and brand equity on business development using religiosity as a moderating variable. This study uses quantitative methods that aim to confirm the data obtained in the field with existing theories. The object of research used is the perpetrators of the Micro and Small and Medium Enterprises (MSMEs) in Semarang Regency with a sample of 100 respondents. As for the data collection technique using the questionnaire method. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The positive influence of religiosity on MSMEs' performance aligns with the findings of Hunjra et al, (2021), stating that religiosity has a positive impact on company performance. Dhea Finka Audy Sukma et al, (2022) revealed that religiosity can moderate the relationship between business motivation and business development. The influence of religiosity on the performance of Micro, Small, and Medium Enterprises (MSMEs) can vary significantly depending on how religiosity is interpreted and integrated into their business operations.…”
Section: Relationships Between Religiosity Islamic Financial Literacy...mentioning
confidence: 99%
“…The positive influence of religiosity on MSMEs' performance aligns with the findings of Hunjra et al, (2021), stating that religiosity has a positive impact on company performance. Dhea Finka Audy Sukma et al, (2022) revealed that religiosity can moderate the relationship between business motivation and business development. The influence of religiosity on the performance of Micro, Small, and Medium Enterprises (MSMEs) can vary significantly depending on how religiosity is interpreted and integrated into their business operations.…”
Section: Relationships Between Religiosity Islamic Financial Literacy...mentioning
confidence: 99%